MENCARI LANDASAN ETIS BAGI UPAYA MEMBUDAYAKAN PENGELOLAAN LINGKUNGAN YANG BERTANGGUNG JAWAB - wilujeng, sri rahayu (HUMANIKA, 2011)
The environment problem is an urgent issue nowadays. Degrading quality of our living environment is a step towards the destruction of the future of human beings. Nature then should be treated humanly with a communal sense of responsibility. This problem is indeed our collective responsibility which involves each individual, family, society, and nation. As a cultural being, all human actions ideally should be based upon morality and ethical values, and this ideal includes how we treat the environment. To cultivate a responsible management of environement thus should be imperative. We find here the fundamental value of environmental ethics in creating a cultured relationship among human beings and their environment.Â Â http://ejournal.undip.ac.id/index.php/humanika/article/view/2902